Investigation of radiation shielding, antibacterial and some properties of nanosilver applied and coated woven fabrics - KODALOĞLU, FEYZA AKARSLAN; OĞUZ, NACİYE SÜNDÜZ (The National Research and Development Institute for Textiles and Leather, 2023)
Antibacterial textiles are widely used in terms of providing hygiene and comfort by protecting human health. Due to its importance in the health sector and increasing customer demands, the trend towards these textiles is increasing day by day. In this study, the antibacterial properties of cotton and cotton/polyester woven fabrics which had applied impregnation and coating processes were examined and compared. For this purpose, nano silver-containing chemicals were applied to the fabrics by impregnation method to give antibacterial properties. After this, the fabrics were coated with tungsten and barium sulphate which have different properties, and coating fabric with antibacterial and radiation shielding properties is obtained. To examine some properties of these antibacterial fabrics, tensile strength, washing fastness, friction fastness tests and SEM analysis were applied to the fabrics. The coating and impregnated fabrics were compared with the fabrics that had been coated only.
Keywords: 3. Good health